Personnel, Acknowledgments - L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2016)
Research Center Personnel, Kansas State University Southeast Agricultural Research Center. Acknowledgments: We thank the following individuals, organizations, and firms that contributed to this year’s research programs through financial support, product donations, or services.